Flexural strength of surface-treated heat-polymerized acrylic resin after repair with aluminum oxide-reinforced autopolymerizing acrylic resin - Shraddha Hareshwar Tamore; K S Jyothi; Seshagiri Muttagi; Amit M Gaikwad (Wolters Kluwer Medknow Publications, 2018)
Background: A fracture of denture base in situ often occurs through a fatigue mechanism, which over a period of time leads to the formation of small cracks, resulting in fracture. Aim and Objective: To evaluate the flexural strength of repaired heat-polymerized acrylic resin, with different percentage of aluminum oxide (Al2O3) added to the repair resin and effect of two different surface treatments on the flexural strength of repaired heat-polymerized acrylic resin and also to evaluate quantification of filler particles using scanning electron microscopy. Materials and Methodology: Fifty specimens of heat-polymerized acrylic resin were prepared according to the American Dental Association specification no. 12 (65 mm × 10 mm × 2.5 mm). Al2O3<50 nm particle size was silanized using metal alloy primer before incorporation in polymer. Two different percentages of Al2O3nanoparticles, that is, 1% and 1.5% were added to autopolymerizing acrylic resin which was used as repairing material. Results: The study showed that repair resin incorporated with 1.5% Al2O3in the group surface treated with silicon carbide paper improved the flexural strength of denture base resin. A proper filler distribution and deep penetration within the polymer matrix were observed by scanning electron microscope in the same group.